WHAT MOTIVATES SECONDARY SCHOOL LEARNERS TO STUDY? - SZABÓ‐THALMEINER NOÉMI (Studia Universitatis Babes-Bolyai, 2016)
ABSTRACT. School performance is determined not only by the learners' cognitive abilities, but also by several other factors, including learner motivation, which provides the necessary energy for learning (Oroszlány, 1994). Experience has proved that learners equipped with very good learning abilities do not achieve their best possible results, while learners with weaker cognitive abilities but more diligence work hard and do better at school. The phenomenon can be explained with the degree and form of motivation for learning, which, if taken into account and developed, can become a tool for fostering achievement. The research tries to find out the characteristics of grammar and high school learners' motivation, using written surveying methods (Kozéki & Entwistle, 1986), and examines whether there are any typical differences based on age group and gender. The questionnaire analyses learner characteristics along three dimensions: social‐ affective, cognitive‐behavioral and moral‐integrative. Based on the research findings, recommendations can be made on how to motivate learners effectively, which teachers of different age groups could use.